The World Bank Approach to Public Sector Management 2011-2020 : Better Results from Public Sector Institutions - World Bank (Washington, DC, 2015)
Public sector management (PSM) reform is concerned with improving public sector results by changing the way governments work. It is a challenging reform area in which to offer assistance. Sustainable institutional change often requires that thousands of public agents alter their behavior, and political incentives may be at odds with improving public sector performance. “What works” in PSM reform is highly context-dependent and explicit evidence remains limited. The Bank’s Approach to PSM for 2011-2020 emphasizes that public sector reform is a pragmatic problem-solving activity, which seeks to improve results by identifying sustainable improvements to the public sector results chain. The Approach reflects continuing evolution in the Bank's PSM work. It responds to changing demands from client countries, as well as changes in the Bank's own operating environment, including opportunities presented by results-based lending and risk management strategies. It puts into practice the lessons learned from significant progress research has made in recent years in unpacking the nature of institutional reform. Overall, it seeks to achieve better results by better adapting the way in which the Bank supports client countries to the distinctive nature of PSM reform.